Targeting the recurrent Rac1P29S neoepitope in melanoma with heterologous high-affinity T cell receptors - Immisch, Lena; Papafotiou, George; Gallarín Delgado, Nerea; Scheuplein, Vivian; Paschen, Annette; Blankenstein, Thomas; Willimsky, Gerald (Frontiers in Immunology, 2023)
Recurrent neoepitopes are cancer-specific antigens common among groups of patients and therefore promising targets for adoptive T cell therapy. The neoepitope FSGEYIPTV carries the Rac1P29S amino acid change caused by a c.85C>T missense mutation, which is the third most common protein-coding hotspot mutation in melanoma. Here, we focused on the isolation and characterisation of TCRs to target this HLA-A*02:01-binding neoepitope by adoptive T cell therapy. Peptide immunisation elicited immune responses in a transgenic mouse model expressing a diverse human TCR repertoire and we successfully isolated high-affinity TCRs. TCR-transduced T cells induced cytotoxicity against Rac1P29S expressing melanoma cell lines and we observed regression of Rac1P29S expressing tumors in vivo after adoptive T cell therapy (ATT). Here we found that a TCR raised against a heterologous mutation with higher peptide-MHC affinity (Rac2P29L) more efficiently targeted the common melanoma mutation Rac1P29S. Overall, our study provides evidence for the therapeutic potential of Rac1P29S-specific TCR-transduced T cells.